Demokrasi di Negara Hukum yang Beretika/Bermoral - Catarina Natasha Manurung (Humaniora, 2011)
Democracy is good, especially which existed in law-based (rechtsstaat) countries and not power-based (machtsstaat) countries. Democracy in law-based country should match the ethic principles and morality so it could run in the right track. Government is based on constitutional system (foundation system) not based on absolutism (unlimited power). Article is about the on-going implementation of democracy in Indonesia; which should suit the democracy values, such as ending argument in peaceful and democratic way, ensuring the peaceful changing in community and holding regular leader’s changing.